Revisiting the Antecedents of Green Marketing Communication: A Pathway towards Sustainability - Singla, Kavita; Thakur, Anand; Kohli, Simriti (Gyan Management Journal, 2023)
Companies these days, are recognizing the relevance of pro environmental marketing strategies in their business practices. But  prevailing malpractices of greenwashing have increased consumers’  scepticism about companies’ green endeavours. Need of the hour is  to effectively communicate genuine sustainable practices to eradicate  brand mistrust and promote ecological behaviour among consumers.Literature Review  Though some efforts have been made in strengthening the literature  on GMC by Chang et al. (2021), Koo et al. (2006), Dinh et al. (2023),  Mao & Zhang (2013). But the integrated framework on the same is  still unavailable.  Purpose of the Study  The present study aims to propose a theoretical framework  conceptualizing the antecedents of Green Marketing Communication  that shape the consumers’ attitude towards GMC. Research Methodology  Based on the exploratory qualitative design, the study proposes and  corroborates various antecedents of GMC drawn from previous  literature.
Keywords: Green Marketing Communication; cognitive; affective; Greenwashing; Environment